Differences in saliva ACE2 activity among infected and non-infected adult and pediatric population exposed to SARS-CoV-2. Issue 1 (July 2022) - Jiménez, Daniel; Martínez-Sanz, Javier; Sainz, Talía; Calvo, Cristina; Méndez-Echevarría, Ana; Moreno, Elena; Blázquez-Gamero, Daniel; Vizcarra, Pilar; Rodríguez, Mario; Jenkins, Robert; Sánchez-Conde, Matilde; Ron, Raquel; et al.
Highlights: ACE2 saliva activity could explain SARS-CoV-2 susceptibility and severity differences. ACE2 activity is lower in the pediatric population compared to adults. Uninfected, highly exposed adults have lower ACE2 activity than those infected. We observe an increase in ACE2 activity as the disease's severity increases. Abstract: Background: Variations in the ACE2 activity in saliva could explain the striking differences of susceptibility to infection and risk of severe disease. Methods: We analyze the activity of ACE2 in saliva in different population groups across a wide age range and disease status during April to June 2020, before SARS-CoV-2 vaccine implementation, and we establish differences between infected people and participants considered resistant (highly exposed healthcare workers and children who cohabited with parents with COVID-19 without isolation and remain IgG negative). Results: We included 74 adults, of which 47 (64%) were susceptible and 27 (36%) were resistant, and 79 children, of which 41 (52%) were susceptible and 38 (48%) were resistant. Resistant adults have significantly lower ACE2 activity in saliva than susceptible adults and non-significant higher values than susceptible and resistant children. ACE2 activity is similar in the susceptible and resistant pediatric population ( p = 0.527). In contrast, we observe an increase in activity as the disease's severity increases among the adult population (mild disease vs. severe disease, 39 vs. 105 FU, p = 0.039; severe disease vs. resistant, 105 vs. 31 FU, p < 0.001). Conclusions: using an enzymatic test, we show that ACE2 activity in saliva correlates with the susceptibility to SARS-Cov-2 infection and disease severity. Children and adults with low-susceptibility to SARS-Cov-2 infection showed the lowest ACE2 activity. These findings could inform future strategies to identify at-risk individuals.